Poker as a riskless investment? - Radu, Valentin (2011)
Poker is considered to be a form of gambling in which luck influences the course and result of the game. However, from a scientific point of view, the element of luck can be proven irrelevant in the long run, if the players use exact sciences in their process of decision making. This Bachelor's thesis analyzes this game and it's importance in history as a consumer good, offering the consumers a certain degree of satisfaction for their demand. It also presents the connection and influences between poker and game theory explaining it's importance in decision making in this game. The body of this thesis explains the application of mathematics and probability in poker and how a player can use them together with statistics to make himself profitable in the long run. Important mathematics based poker theories issued by multiple world champions and their use in the decision of the players are also explained along with how their use can advert the factor of luck and offer a high degree of certainty to the subjects involved in the uncertain game. Finally the thesis researches the economics of poker from the players point of view, but also the giant corporations of this, multinational billion dollar industry, which bring this good to the market for individuals.